Method for determining thickness of concrete interface transition area based on nano scratches

By using nano-scratching technology to obtain the boundary points of the concrete interface transition zone, and using derivatives and fitting functions to calculate the thickness, the problem of insufficient accuracy caused by discontinuous measurement points and subjective selection in existing technologies is solved. This enables continuous and accurate measurement of the thickness of the interface transition zone, which is suitable for dynamic monitoring of thickness during the deterioration process and improves the thickness monitoring effect.

CN121049074APending Publication Date: 2025-12-02RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +1

Patent Information

Application Number
CN202511335041.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing technologies for measuring the thickness of the transition zone at the concrete interface suffer from problems such as discontinuous measurement points and insufficient accuracy due to subjective selection of boundary points, lacking a scientific, accurate, and continuous measurement method.

Method used

Using nano-scratching technology, the sample to be tested is pre-treated and then pre-scanned, scratched, and post-scanned using a nano-scratching tester to obtain the average curve of scratch depth-scratching distance. The boundary points of the interface transition zone are extracted by fitting the first derivative, second derivative, and sine function, and the thickness is calculated. The results are verified by fracture toughness.

Benefits of technology

It enables continuous and accurate measurement of the thickness of the concrete interface transition zone, avoiding boundary misjudgment in traditional methods. It is suitable for dynamic monitoring of thickness during the deterioration process, improving the objectivity and accuracy of thickness calculation. It is particularly suitable for dynamic monitoring of thickness, improving the monitoring accuracy of thickness and making it effective for thickness measurement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121049074A_ABST
    Figure CN121049074A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a method for determining the thickness of a concrete interface transition area based on nano scratches, which comprises the following steps: pretreating a to-be-detected sample; the method comprises the following steps: testing a to-be-tested sample through scanning based on a nano scratch tester to obtain a scratch depth-scratch distance mean value curve; based on the scratch depth-scratch distance mean value curve, boundary points between the base body and the interface transition area and boundary points between the interface transition area and aggregate are extracted, and the thickness of the interface transition area is calculated; calculating a fracture toughness mean value based on the scratch depth characterization value and the transverse scratch load, and drawing a fracture toughness-scratch distance mean value curve; and putting the boundary points into the fracture toughness-scratch distance mean value curve, and verifying the calculated thickness of the interface transition area. According to the invention, continuous and accurate measurement of the ITZ thickness is realized based on the difference between mechanical properties of different phases, and a scientific tool is provided for dynamic evaluation of concrete durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, and more specifically to a method for determining the thickness of the transition zone at the concrete interface based on nano-scratching. Background Technology

[0002] The interfacial transition zone, due to its high porosity and high calcium hydroxide orientation index, becomes a weak area in the internal mechanical properties of concrete. Under external loads or environmental erosion, the interfacial transition zone tends to deteriorate preferentially, manifested as the initiation and propagation of microcracks and a decrease in interfacial bond strength. Furthermore, the average thickness of the interfacial transition zone increases significantly during the deterioration process, creating a vicious cycle that accelerates material performance degradation. Therefore, accurately calculating the thickness of the concrete interfacial transition zone during the deterioration process is of great significance for assessing the durability and long-term performance of concrete.

[0003] Nano-scratching technology enables continuous measurement of the micromechanical properties of concrete. The longitudinal load F applied by the scratching probe as it scratches along the material surface... N When the probe's moving speed remains constant, the differences in the micromechanical properties of different phases are mainly manifested in the scratch depth of the probe and the lateral force F required for the probe to move. T The difference lies in the degree of scratches. When concrete deteriorates, the scratch depth in the interfacial transition zone increases significantly, while the fracture toughness decreases. Currently, researchers mainly determine the thickness of the interfacial transition zone between clinker and hydration products, fibers and matrix, and paste and aggregate by analyzing the friction coefficient between the scratch probe and the material under test, the scratch depth, and the distribution characteristics of fracture toughness. However, a systematic mathematical characterization method has not yet been established.

[0004] Currently, the thickness characterization of the transition zone at the concrete interface relies mainly on scanning electron microscopy or micromechanical property testing, and the thickness range is determined by manually defining the boundaries of micromorphological differences and image analysis. CN113155042B discloses a method for measuring the thickness of the transition zone at the interface of concrete. This method involves pressing a test block and capturing deformation images using a CCD camera. It then analyzes the displacement field cloud map using digital image processing (Vic-2D) and determines the boundary of the interface transition zone based on the slope inflection point of the displacement curve, and calculates the thickness. However, this method does not involve the dynamic characterization of the micro-porosity of the interface transition zone, and the selection of its slope abrupt change point is somewhat subjective. CN117629709A discloses a method for continuously measuring the indentation modulus of the transition zone at the interface of concrete. It calculates a continuous function of the contact stiffness as a function of the indentation depth by using the ratio of the harmonic force amplitude to the harmonic displacement amplitude and the phase difference between the two. It analyzes the change of the indentation modulus with depth to delineate the boundary of the interface transition zone. However, this method does not essentially use a continuous measurement point approach. It can only obtain the micro-mechanical properties of the phase by measuring at intervals, which may lead to a large dispersion in the calculated thickness of the interface transition zone.

[0005] Therefore, how to provide a scientific, accurate, and continuously measurable method for determining the thickness of the concrete interface transition zone is a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0006] To address the shortcomings of existing testing technologies, such as discontinuous measurement points and insufficient accuracy due to subjective selection of boundary points, this invention aims to provide a scientific, accurate, and continuously measurable method for calculating the thickness of the transition zone at concrete interfaces.

[0007] To achieve the above objectives, the present invention adopts the following technical solution:

[0008] A method for determining the thickness of the transition zone at a concrete interface based on nano-scratching, characterized by comprising:

[0009] Pre-treatment of the sample to be tested;

[0010] Based on a nano-scratch tester, the test sample is scanned to obtain the average curve of scratch depth-scratch distance;

[0011] The boundary points of the matrix and the interface transition zone, as well as the boundary points of the interface transition zone and the aggregate, are extracted based on the average curve of scratch depth-scratch distance, and the thickness of the interface transition zone is calculated.

[0012] Preferably, the sample to be tested is a prism or cylinder with a diameter of less than 30 mm and a height of less than 9 mm;

[0013] The top and bottom surfaces of the sample were inlaid with epoxy resin and then polished using a fully automatic polishing machine.

[0014] Preferably, the method also includes testing the sample based on a nano-scratch tester and performing pre-scanning and post-scanning.

[0015] Preferably, when testing the sample to be tested using a nano-scratch tester and through three stages of pre-scanning, etching scan and post-scanning, the longitudinal load applied during the pre-scanning and post-scanning stages is less than or equal to 25 μN, and the longitudinal load applied during the etching scan is 30 mN to 100 mN.

[0016] Preferably, during the scratching and scanning stage, the scratch length of the entire scratching process is 180μm to 240μm. Starting from the matrix area, the scratches successively pass through the interface transition zone and the aggregate. Each sample to be tested is subjected to three scratch tests, forming three parallel scratch tracks with a spacing of 40μm to 60μm on the surface of the sample to be tested.

[0017] The mean curve of scratch depth versus scratch distance was obtained based on three parallel scratch trajectories.

[0018] Preferably, the boundary points of the matrix and interface transition zone, as well as the boundary points of the interface transition zone and aggregate, are extracted based on the average curve of scratch depth-scratch distance. The thickness of the interface transition zone is then calculated, including:

[0019] From the trough of the scratch depth-scratch distance curve, select the extreme points where the first derivative is 0 and the second derivative is greater than 0 as the temporary boundary points of the interface transition zone and the aggregate, and select the extreme points where the first derivative is 0 and the second derivative is less than 0 as the temporary boundary points of the matrix and the interface transition zone.

[0020] Calculate the average scratch depth in the region to the left of the temporary boundary point of the matrix and interface transition zone, and draw its straight line L1. Calculate the average scratch depth in the region to the right of the temporary boundary point of the interface transition zone and aggregate, and draw its straight line L2.

[0021] Obtain the intersection of the curve corresponding to the left region of the temporary boundary point between the matrix and the interface transition zone with the straight line L1, and the intersection of the curve corresponding to the right region of the temporary boundary point between the interface transition zone and the aggregate with the straight line L2.

[0022] From the scratch depth-scratch distance curve region corresponding to the two temporary boundary points, select the inflection point where the second derivative is 0;

[0023] Find the point symmetrical to the intersection of line L1 with respect to the inflection point, and the point symmetrical to the intersection of line L2 with respect to the inflection point;

[0024] A sine function curve is obtained based on the intersection point, inflection point, and symmetric point of the intersection point of line L1 about the inflection point. The intersection point of the tangent line of this sine function curve with line L1 is the boundary point of the transition zone between the matrix and the interface.

[0025] A sine function curve is obtained based on the intersection point, inflection point, and symmetrical point of the intersection point of line L2 about the inflection point. The intersection point of the tangent line of this sine function curve with line L2 is the interface transition zone and the boundary point of the aggregate.

[0026] The thickness of the interface transition zone is obtained based on two boundary points.

[0027] Preferred options also include:

[0028] The fracture toughness value is calculated based on the scratch depth characterization value and the transverse scratch load of the scratch scanning stage. Three fracture toughness-scratch distance curves corresponding to the three scratch trajectories of the scratch scanning stage are obtained. After processing, the mean curve of fracture toughness-scratch distance is obtained.

[0029] By substituting the boundary points into the mean curve of fracture toughness versus scratch distance, the calculated thickness of the interface transition zone is verified. Preferably, the formula for calculating the fracture toughness value is:

[0030]

[0031] Among them, K c F represents the fracture toughness value. T d represents the lateral scratch load during the scanning stage, and d represents the scratch depth characterization value.

[0032] As can be seen from the above technical solution, compared with the prior art, the present invention discloses a method for determining the thickness of the transition zone of a concrete interface based on nano-scratching, which has the following advantages:

[0033] (1) This invention realizes the continuous acquisition of micro-mechanical parameters, fully captures the gradient change characteristics of mechanical properties in the interface transition zone, avoids boundary misjudgment caused by traditional discrete measurement points, and uses mathematical methods such as first derivative, second derivative function and symmetric sine fitting to accurately extract the boundary points of the interface transition zone, which significantly improves the objectivity and accuracy of thickness calculation, and is especially suitable for monitoring the dynamic changes of thickness during the deterioration process.

[0034] (2) The quantitative characterization method of the thickness of the transition zone of concrete interface in this invention is simple and easy to operate, and has rigorous logic.

[0035] (3) In the present invention, the maximum load of the probe on the sample during the nano-scratch test is less than 10N, and the mechanical property test of the sample is close to non-destructive testing. It can be repeatedly monitored or used for other microscopic property tests. Attached Figure Description

[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0037] Figure 1 This is a flowchart of a method for determining the thickness of the transition zone at a concrete interface based on nano-scratching, according to the present invention.

[0038] Figure 2 This is an electron microscope image of the scratch trajectory of the present invention through the matrix, interface transition zone, and aggregate.

[0039] Figure 3 This is a schematic diagram illustrating the preliminary determination of the interface transition zone thickness based on the average curve of scratch depth and scratch distance according to the present invention.

[0040] Figure 4 This is a precise schematic diagram illustrating the quantitative characterization of the thickness of the interface transition zone according to the present invention.

[0041] Figure 5 This is a schematic diagram of the microscopic fracture toughness-scratch distance curve drawn by the present invention to verify the accuracy of the results. Detailed Implementation

[0042] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0043] This invention discloses a method for determining the thickness of the transition zone at a concrete interface based on nano-scratching, such as... Figure 1 As shown, it includes:

[0044] Pre-treatment of the sample to be tested;

[0045] Based on a nano-scratch tester, the test sample is scanned to obtain the average curve of scratch depth-scratch distance;

[0046] Based on the average value curve of scratch depth-scratch distance, the boundary points between the matrix and the interface transition zone, as well as the boundary points between the interface transition zone and the aggregate, are extracted, and the thickness of the interface transition zone is calculated.

[0047] The fracture toughness value is calculated based on the scratch depth characterization value and the transverse scratch load during the scratching stage, and the mean curve of fracture toughness-scratch distance is plotted.

[0048] By placing the boundary points into the mean curve of fracture toughness-scratch distance, the thickness of the calculated interface transition zone is verified.

[0049] The method for determining the thickness of the concrete interface transition zone in this invention is based on the mechanical gradient response principle of nano-scratching technology: Concrete consists of a matrix, aggregate, and interface transition zone, and the microscopic mechanical properties of the three components differ significantly; when a probe scratches the concrete material, the interface transition zone experiences abrupt changes in scratch depth and fluctuations in lateral load due to its weak mechanical properties; this invention can accurately characterize the thickness of the interface transition zone by analyzing the mathematical characteristics (derivative extrema, symmetrical fitting boundary) of the scratch depth-distance curve.

[0050] In this embodiment, the concrete sample to be tested is a prism with a diameter of less than 30 mm and a height of less than 9 mm. More preferably, in this embodiment, the prism sample is cut from the surface into a size of 15 mm × 15 mm × 8 mm. Then, the top and bottom surfaces of the obtained 15 mm × 15 mm prism sample are polished using a precision grinding machine to make the two surfaces parallel. After that, the polished top and bottom surfaces are inlaid with epoxy resin. Finally, the inlaid sample is polished using a fully automatic polishing machine.

[0051] In this embodiment, the scratch tester used is the Keysight G200 nano-scratch tester equipped with a Berkovich probe, and its technical parameters meet the following requirements:

[0052] 1) Equipped with a Berkovich probe with a displacement resolution of less than 0.01 nm;

[0053] 2) The maximum load that the probe can apply is 10N;

[0054] 3) The displacement accuracy of adjacent measuring points is less than 0.01 nm.

[0055] The entire scratch test consists of three stages: pre-scan, scratch scan, and post-scan. The longitudinal load applied during the pre-scan and post-scan phases is less than or equal to 25 μN, for example, it could be F. N =20μN, the longitudinal load applied during the etching scan is 30mN~100mN, specifically F N =50±0.5mN. The purpose of the pre-scan is to eliminate the influence of initial surface unevenness of the sample and provide a precise positional reference. The purpose of the post-scan is to directly measure the residual depth, assess elastic recovery, and visualize damage patterns.

[0056] The core value of pre-scanning and post-scanning lies in their comparison. Only through subtraction can the true and accurate depth of plastic deformation (residual depth) caused by the scratch and the depth of the deformation process be obtained; the smaller the difference, the more reliable the result. Pre-scanning and post-scanning do not contribute to determining the thickness of the interface transition zone in this invention; they are merely requirements of the experiment itself.

[0057] During the scanning stage, the scratch area is selected using an electron microscope, ensuring that the scratch trajectory starts from the mortar matrix and sequentially passes through the interface transition zone and aggregate. Three scratch tests are performed on the test area, with each scratch being 200 μm in length and spaced 60 μm apart. Figure 2 As shown.

[0058] In this embodiment, the specific data processing steps are as follows:

[0059] (1) After the scratch test is completed, export the data and select the longitudinal load F during the scratch scanning stage. N The scratch depth data at 50±0.5mN was imported into Origin to plot the scratch depth-scratch distance curve. The scratch depth data corresponding to the three scratch trajectories obtained during the scribing and scanning stage were arithmetically averaged using 2D Smoother. The arithmetic mean was used as the scratch depth characterization value of the sample under test, and the scratch depth-scratch distance mean curve was obtained at the same time to reduce dispersion.

[0060] (2) The interface transition zone is a weak area of ​​concrete material, and the probe scratches deepest in this zone. The boundary point between the aggregate and the interface transition zone is called P1, and the boundary point between the interface transition zone and the matrix is ​​called P2. The troughs in the average scratch depth-scratch distance curve are selected to initially identify boundary points P1 and P2. When the curve is to the left of P1, it increases slowly; when it is to the right of P2, it decreases. Therefore, P1 must satisfy… Accordingly, P2 needs to satisfy f(X) p2 >0. Through analysis of the first and second derivatives, the temporary boundary points satisfying the boundary points P1 and P2 can be determined to be A and C, respectively. Therefore, the region to the left of curve A can be labeled Mortar', the region to the right of C as AGG', and the region between A and C as ITZ', as shown below. Figure 3 As shown in (a).

[0061] Calculate the average scratch depth of Mortar' and AGG' respectively, and plot the straight lines L1 and L2 of the average scratch depth of the two phases in the figure, intersecting the curves of the two phase regions at E, F and G, H respectively, as shown. Figure 3 As shown in (b).

[0062] Select the inflection point D(f) from ITZ'. D=0). Find the centrally symmetric points E', F', G', and H' of points E, F, G, and H about the inflection point D, and the symmetric lines L'1 and L'2 of lines L1 and L2 about point D. Finally, perform sine fitting on E, F, D, E', F' and G, H, D, G', H' respectively to obtain two sine function curves, as shown. Figure 4 As shown in (a).

[0063] Draw tangents to the two sine curves through point D, intersecting lines L1 and L2 at points I and J, respectively. I is the boundary point between the matrix and the interface transition zone, and J is the boundary point between the interface transition zone and the aggregate. The lateral distances between point D and points I and J are T1 and T2, respectively, where T1 and T2 are the thicknesses of the interface transition zone near the matrix and aggregate sides, respectively. Finally, the thickness of the interface transition zone is T1 + T2, as shown below. Figure 4 As shown in (b), (c), and (d).

[0064] Plotting microfracture toughness-scratch distance curves based on scratch depth d and transverse scratch load F T Then by Calculate the fracture toughness value K c Plot the fracture toughness-scratch distance curves. Based on the three fracture toughness-scratch distance curves, obtain the mean curve of the fracture toughness-scratch distance.

[0065] To verify the accuracy of the results, boundary points I and J were substituted into the mean curve of microscopic fracture toughness-scratch distance. The region between boundary points I and J represents the bottom of the curve. Figure 5 As shown, the results are reliable.

[0066] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since they correspond to the methods disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to the method section.

[0067] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for determining the thickness of the transition zone at a concrete interface based on nano-scratching, characterized in that, include: Pre-treatment of the sample to be tested; Based on a nano-scratch tester, the test sample is scanned to obtain the average curve of scratch depth-scratch distance; The boundary points of the matrix and the interface transition zone, as well as the boundary points of the interface transition zone and the aggregate, are extracted based on the average curve of scratch depth-scratch distance, and the thickness of the interface transition zone is calculated.

2. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 1, characterized in that, The sample to be tested is a prism or cylinder with a diameter of less than 30 mm and a height of less than 9 mm; The top and bottom surfaces of the sample were inlaid with epoxy resin and then polished using a fully automatic polishing machine.

3. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 1, characterized in that, It also includes testing the sample based on a nano-scratch tester and through pre-scanning and post-scanning.

4. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 3, characterized in that, When testing the sample using a nano-scratch tester through three stages—pre-scan, etching scan, and post-scan—the longitudinal load applied during the pre-scan and post-scan stages is less than or equal to 25 μN, while the longitudinal load applied during the etching scan stage is 30 mN to 100 mN.

5. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 1, characterized in that, During the scratching and scanning stage, the scratch length of the entire scratching process is 180μm to 240μm. Starting from the matrix area, it successively scratches the interface transition area and the aggregate. Each sample to be tested is subjected to three scratch tests, forming three parallel scratch tracks with a spacing of 40μm to 60μm on the surface of the sample to be tested. The mean curve of scratch depth versus scratch distance was obtained based on three parallel scratch trajectories.

6. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 1, characterized in that, Based on the scratch depth-scratch distance mean curve, the boundary points of the matrix and interface transition zone, as well as the boundary points of the interface transition zone and aggregate, are extracted. The thickness of the interface transition zone is then calculated, including: From the trough of the average value curve of scratch depth-scratch distance, select the extreme point where the first derivative is 0 and the second derivative is greater than 0 as the temporary boundary point of the interface transition zone and the aggregate, and select the extreme point where the first derivative is 0 and the second derivative is less than 0 as the temporary boundary point of the matrix and the interface transition zone. Calculate the average scratch depth in the region to the left of the temporary boundary point of the matrix and interface transition zone, and draw its straight line L1. Calculate the average scratch depth in the region to the right of the temporary boundary point of the interface transition zone and aggregate, and draw its straight line L2. Obtain the intersection of the curve corresponding to the left region of the temporary boundary point between the matrix and the interface transition zone with the straight line L1, and the intersection of the curve corresponding to the right region of the temporary boundary point between the interface transition zone and the aggregate with the straight line L2. From the region of the average scratch depth-scratch distance curves between two temporary boundary points, select the inflection point where the second derivative is 0; Find the point symmetrical to the intersection of line L1 with respect to the inflection point, and the point symmetrical to the intersection of line L2 with respect to the inflection point; A sine function curve is obtained based on the intersection point, inflection point, and symmetric point of the intersection point of line L1 about the inflection point. The intersection point of the tangent line of this sine function curve with line L1 is the boundary point of the transition zone between the matrix and the interface. A sine function curve is obtained based on the intersection point, inflection point, and symmetrical point of the intersection point of line L2 about the inflection point. The intersection point of the tangent line of this sine function curve with line L2 is the interface transition zone and the boundary point of the aggregate. The thickness of the interface transition zone is obtained based on two boundary points.

7. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 6, characterized in that, Also includes: The fracture toughness value is calculated based on the scratch depth characterization value and the transverse scratch load of the scratch scanning stage. Three fracture toughness-scratch distance curves corresponding to the three scratch trajectories of the scratch scanning stage are obtained. After processing, the mean curve of fracture toughness-scratch distance is obtained. By substituting the boundary points into the mean curve of fracture toughness-scratch distance, the thickness of the calculated interface transition zone is verified.

8. The method for determining the thickness of the concrete interface transition zone based on nano-scratching according to claim 7, characterized in that, The formula for calculating fracture toughness is: Among them, K c F represents the fracture toughness value. T d represents the lateral scratch load during the scanning stage, and d represents the scratch depth characterization value.

Citation Information

Patent Citations

  • A method for measuring the thickness of the transition zone at the inner interface of concrete.

    CN113155042B

  • Method for continuously measuring indentation modulus of interface transition area in concrete

    CN117629709A

Cited By

  • Method and device for measuring thickness of soft rock area after long-term flow guide of crack

    CN122150544A